Systematics of the Little Red Tree Frog, Litoria rubella (Anura: Pelodryadidae), with the description of two new species from eastern Australia and arid Western Australia - Purser, William A.; Doughty, Paul; Rowley, Jodi L.; Böhme, Wolfgang; Donnellan, Stephen C.; Anstis, Marion; Mitchell, Nicola; Shea, Glenn M.; Amey, Andrew; Mitchell, Brittany A.; Catullo, Renee A. (Zootaxa, 2025)
The Litoria rubella species complex (L. capitula and L. rubella) is distributed across much of continental Australia, southern New Guinea, and the Tanimbar Islands of Indonesia, in habitats ranging from deserts to tropical forests. We carried out an appraisal of molecular genetics, advertisement calls, and morphological variation in the species complex. Analyses of thousands of nuclear gene SNPs and nucleotide sequences from the mitochondrial ND4 gene identified four reciprocally monophyletic lineages in both marker types, two exclusively in Australia, one in Australia/New Guinea and one from the Tanimbar Islands. The advertisement calls of the three lineages on continental Australia have overlapping but significant differences in the number of pulses in the notes, dominant frequency, and call duration, particularly where the lineages come into contact. The Tanimbar Islands lineage is genetically and morphologically distinct and represents L. capitula. Molecular and advertisement call data together support the recognition of three species in Australia: a widespread central arid and northern tropics lineage, a western arid zone lineage, and an eastern mesic lineage. Litoria rubella sensu stricto is widespread across the tropical Kimberley and Top End regions, southern New Guinea, the central arid zone, and the Murray Darling Basin, making it an extreme climate-generalist. SNP data indicates that L. rubella has gene flow to the north of the Lake Eyre Basin but not the south, making it a possible ring species. The western arid zone lineage does not differ in appearance or advertisement call from L. rubella but is geographically disjunct and phylogenetically distinct. The eastern lineage is primarily distributed to the east of the Great Dividing Range and Cape York in Queensland. We redescribe L. rubella sensu stricto, describe the eastern lineage and western arid lineage as new species, L. pyrina sp. nov. and L. larisonans sp. nov. respectively. Although L. rubella and L. larisonans sp. nov. are morphologically similar, they do not overlap in distribution, making identification non-problematic. Litoria pyrina sp. nov. can be distinguished from L. rubella at contact zones by having advertisement calls with a higher dominant frequency. We investigated the history and morphology of the type for L. mystacina and designate it a nomen dubium. The three Australian species are likely to have a conservation status of Least Concern as they are widespread and abundant, with no significant threats. Little is known about L. capitula from the Tanimbar Islands outside of the few existing museum specimens.